Brackish ground water and dairy wastewater treatment using electrodialysis system. Issue 1 (May 2021) - Ankoliya, Dipak; Mudgal, Anurag; Sinha, Manish Kumar; Patel, Vivek; Patel, Jatin
Abstract: For brackish water desalination, there is necessity to reduce the volume of saline waste water generated in existing processes due to scarcity of water and to cope up with increasing water demand. The electrodialysis process typically known for its higher water recovery rate with competitive energy consumption per unit volume of clean water produced. Theoretical and experimental investigation of electrodialysis in the feed water composition of Indian ground water would make this technology more adaptable at commercial level. With the capability of bipolar membrane to split water into hydroxide ions and protons, the electrodialysis with bipolar membrane process can produce acid and base solution from the corresponding salt solution. This onsite acid and base production capacity of electrodialysis with bipolar membrane process reduces the need of purchasing these chemicals and also reduces the saline wastewater generation in many industries including dairy industry. This research is aimed to study the electrodialysis system at pilot plant scale installation along with long term testing would make this technology one step ahead in desalination and wastewater treatment.